2021
DOI: 10.5194/amt-14-5717-2021
|View full text |Cite
|
Sign up to set email alerts
|

A simulation-experiment-based assessment of retrievals of above-cloud temperature and water vapor using a hyperspectral infrared sounder

Abstract: Abstract. Measuring atmospheric conditions above convective storms using spaceborne instruments is challenging. The operational retrieval framework of current hyperspectral infrared sounders adopts a cloud-clearing scheme that is unreliable in overcast conditions. To overcome this issue, previous studies have developed an optimal estimation method that retrieves the temperature and humidity above high thick clouds by assuming a slab of cloud. In this study, we find that variations in the effective radius and d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(31 citation statements)
references
References 57 publications
(85 reference statements)
0
31
0
Order By: Relevance
“…The high spectral resolution in the mid-infrared makes AIRS sensitive to temperature, water vapor, and also clouds. However, the standard AIRS retrieval is not sensitive to the water vapor signal from the UTLS (Fetzer et al, 2008;Gettelman et al, 2004;Read et al, 2007) because of the weak absorption and/or emission of the dry UTLS relative to the troposphere and a cloud-clearing algorithm (Susskind et al, 2003) adopted by the AIRS standard retrieval. This algorithm infers temperature and trace gases of the clear-sky portion of adjacent 3 × 3 FOVs with varying cloud amounts by contrasting the nine FOVs, assuming a uniform distribution of these atmospheric states.…”
Section: Datasetsmentioning
confidence: 99%
See 4 more Smart Citations
“…The high spectral resolution in the mid-infrared makes AIRS sensitive to temperature, water vapor, and also clouds. However, the standard AIRS retrieval is not sensitive to the water vapor signal from the UTLS (Fetzer et al, 2008;Gettelman et al, 2004;Read et al, 2007) because of the weak absorption and/or emission of the dry UTLS relative to the troposphere and a cloud-clearing algorithm (Susskind et al, 2003) adopted by the AIRS standard retrieval. This algorithm infers temperature and trace gases of the clear-sky portion of adjacent 3 × 3 FOVs with varying cloud amounts by contrasting the nine FOVs, assuming a uniform distribution of these atmospheric states.…”
Section: Datasetsmentioning
confidence: 99%
“…Using the wavenumber-dependent cloud extinction coefficients in the mid-infrared channels, this method marginally updates the concentration and effective particle size of ice clouds relative to the collocated cloud observations of active sensors. The effective radius is esti-mated as a vertically averaged value that produces the most reasonable mid-infrared emission spectra of thick high-level clouds (Feng et al, 2021). Through a simulation experiment, Feng et al (2021) demonstrated that the synergistic method is sensitive to spatial variability in thermodynamic conditions above deep convection.…”
Section: Datasetsmentioning
confidence: 99%
See 3 more Smart Citations